2002
DOI: 10.1128/jvi.76.9.4350-4356.2002
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Virus Suppresses Monocyte-to-Macrophage Maturation In Vitro

Abstract: To analyze the pathogenetic mechanism of hematopoietic dysregulation associated with hepatitis A virus (HAV) infections, we studied the influence of HAV on monocyte (MO)-to-macrophage (MAC) maturation in vitro. Exposure of peripheral blood-derived mononuclear cells (MNC) to HAV led to diminished adherence of MO to plastic. Furthermore, HAV inhibited the ability of peripheral blood MO to differentiate toward MAC. Freshly isolated and 14-day-old MO cultures demonstrated reduced differentiation and decreased phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…It is still unknown which mechanisms are related to suppression of CD3/CD4+/CD25+ T cells; HAV might have a direct activity on CD4+/CD25+ T cells' function as already reported for monocytes, 16 or it might be able to mediate the suppression of Tregs through some other cell subsets involving different mechanisms, as previously reported in other diseases 17,18 . In fact, it was of note that once the virus was cleared, after IgG seroconversion, the function of those T lymphocytes was restored to that of healthy individuals.…”
Section: Discussionmentioning
confidence: 86%
“…It is still unknown which mechanisms are related to suppression of CD3/CD4+/CD25+ T cells; HAV might have a direct activity on CD4+/CD25+ T cells' function as already reported for monocytes, 16 or it might be able to mediate the suppression of Tregs through some other cell subsets involving different mechanisms, as previously reported in other diseases 17,18 . In fact, it was of note that once the virus was cleared, after IgG seroconversion, the function of those T lymphocytes was restored to that of healthy individuals.…”
Section: Discussionmentioning
confidence: 86%
“…These results suggested that monocytic THP-1 cells were morphologically and functionally differentiated to macrophages by IV-infected apoptotic cells because of a soluble factor released from the apoptotic cells [50,51]. But, Brucella virus (Brucella genus) can prevent macrophage apoptosis [52,53]. Jimenez et al have shown that B. suis infection inhibits the spontaneously occurring apoptosis in human monocytes/macrophages [52].…”
Section: Effects Of Engulfed Apoptotic Cells On Macrophagesmentioning
confidence: 99%
“…These cells play an indispensable role in regulating the interplay between innate and adaptive immune responses. Viral infections can modulate host immune responses by either enhancing or dampening the effector functions of macrophages, causing immunopathogenesis and/or immunoevasion (Biggs et al, 1995;Kedzierska et al, 2002;Wunschmann et al, 2002). Additionally, macrophages can also harbor infectious viruses, serving as reservoirs for further dissemination (Orenstein, 2001;Way et al, 2002).…”
mentioning
confidence: 99%